Education of Roma Youth in Hungary: Schools, Identities and Belonging. Issue 1 (2nd January 2017) - Dunajeva, Jekatyerina
Abstract : Historically, schools have been homogenizing institutions that often disadvantaged people of color and ethnic and religious minorities. In this article I examine Roma education in Hungary, focusing on (re)production of racial identities and the negotiation of ethnic labels. I distinguish two models of education as they relate to ideas of integration, and assess the evolving ethnic labels: "bad Gypsies" and "good Roma." These labels reflect different philosophies of education, and both contain different tensions and challenges.